2020
DOI: 10.1055/s-0040-1705107
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation, and Validation of a Pediatric ICU Sepsis Prediction Tool as Clinical Decision Support

Abstract: Background Sepsis is an uncontrolled inflammatory reaction caused by infection. Clinicians in the pediatric intensive care unit (PICU) developed a paper-based tool to identify patients at risk of sepsis. To improve the utilization of the tool, the PICU team integrated the paper-based tool as a real-time clinical decision support (CDS) intervention in the electronic health record (EHR). Objective This study aimed to improve identification of PICU patients with sepsis through an automated EHR-based CDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Vidrine et al 8 implemented a sepsis alert in the pediatric intensive care unit (ICU) and found a sepsis alert in this context improved time between physiologic indicators of sepsis and clinical action. Dewan et al 9 also implemented a sepsis prediction tool and clinical decision support in the pediatric intensive care setting and found that the alert had adequate sensitivity and specificity to identify severe sepsis. Other estimates of embedded sepsis alerts have demonstrated adequate predictive values as a tool to identify cases of severe sepsis.…”
mentioning
confidence: 99%
“…Vidrine et al 8 implemented a sepsis alert in the pediatric intensive care unit (ICU) and found a sepsis alert in this context improved time between physiologic indicators of sepsis and clinical action. Dewan et al 9 also implemented a sepsis prediction tool and clinical decision support in the pediatric intensive care setting and found that the alert had adequate sensitivity and specificity to identify severe sepsis. Other estimates of embedded sepsis alerts have demonstrated adequate predictive values as a tool to identify cases of severe sepsis.…”
mentioning
confidence: 99%
“…The remaining 5 pediatric studies [ 73 , 74 , 80 , 82 , 83 ], all conference abstracts, did not specify the CCDS system criteria used for sepsis case identification and were not included in Table 3 . A total of 2 particular systems appear to be the subject of more than one study: the first in the studies by Dewan et al [ 61 ] and Vidrine et al [ 81 ] and the second in the studies by Stinson et al [ 77 ] and Viteri et al [ 82 ]. One journal article [ 64 ] is counted twice in Table 3 , as it contains 2 separate electronic CCDS systems with different criteria: one with automated continuous screening and the other with clinician-initiated screening.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, we present the first interoperable CDSS for detection of pediatric SIRS that has been successfully evaluated in a clinical-driven study, using routine data, broad eligibility criteria for patients of all pediatric ages and underlying diseases, and an appropriate reference standard. Previous CDSS rather tried to optimize SIRS criteria or were using non-specific sepsis criteria, often with impressive results [ 15 , 19 , 20 ]; other approaches aimed at predicting severe sepsis [ 16 , 18 ] or improving time to goal-directed therapy [ 17 ]. All these studies focused on recognizing severe sepsis or septic shock directly instead of SIRS as the initial clinical feature; some used their own criteria differing from the IPSCC definition or set different age ranges, excluding newborns, infants or young adults, thereby limiting the routine (re)use of such system [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these studies focused on recognizing severe sepsis or septic shock directly instead of SIRS as the initial clinical feature; some used their own criteria differing from the IPSCC definition or set different age ranges, excluding newborns, infants or young adults, thereby limiting the routine (re)use of such system [ 14 ]. Often, the reference standard used seems problematic such as in Dewan et al [ 15 ], who chose initiated treatment as reference. The documented time of treatment might not reflect the clinically relevant time as SIRS onset is often missed during clinical routine, as underlined by our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation